Implementation of User Transaction Services Via E-Money Id- Card as a Means of Payment Transactions (Case Study of the Muhammadiyah Zaenab Masykur Islamic Boarding School) - Istiyah, Iin; Putri, Nurul Wulandari (International Journal of Economics, Business Management and Accounting (IJEBMA), 2024)
Advances in the financial and banking system in the economy have been able to shift payment methods from using cash to non-cash forms. E-money is currently popular among all groups, including Islamic boarding schools. The aim of this research is to find out how to implement the use of e-money ID-cards at the Zaenab Masykur Islamic boarding school, Adiwerna. This research uses qualitative methods with data sources coming from interviews and observations. The results of this research show that the use of a manual payment system is felt to be less effective so that e-money becomes a solution to simplify transactions, record and report more quickly and practically. The e-money ID-card is included in the open loop category because it functions as a means of payment, it is a chip based registered type because the user's identity and the value of the money in it are recorded on the holder’s card and registerd. Understanding of technology and concerns about system security as well as limitations in the use of T-cards which can only be used in Islamic boarding schools are challenges in using e-money at Islamic boarding school Zaenab Masykur